Answer:
B
Step-by-step explanation:
In an artihmetic sequence, there is a constant difference between two consecutive terms.
So for instance:
[tex]-6 -(-3) = -3[/tex]
[tex]-3 -0 = -3[/tex]
[tex]0 - 3 = -3[/tex]
As you can see there is a difference of [tex]-3[/tex] from one term to the next
____________________________
You can also find the constant difference the other way around, for instance
[tex]3-0=3[/tex]
[tex]0-(-3) = 3[/tex]
[tex]-3-(-6) = 3[/tex]
In this example, you can see that each term is [tex]3[/tex] higher than the previous term
I hope this helps!!